With Great Data Comes Great Responsibility: How Data Science Can Be Applied to Solve Public Interest Problems Without Losing Its Soul. Issue 1 (2nd January 2018) - Mann, Gideon; Sahuguet, Arnaud
ABSTRACT: Data science has had a tremendous impact in the private sector and is increasingly being applied in the public sector. The Data for Good Exchange (D4GX) is an annual conference centered on these novel problems and applications. This article describes the history of the conference and introduces a selection of the best papers from the 2017 conference that focus on human services.